2017
DOI: 10.48550/arxiv.1708.05668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Dimensional Clustering of Gamma-Ray Bursts using durations and hardness

Aishwarya Bhave,
Soham Kulkarni,
Shantanu Desai
et al.

Abstract: Gamma-Ray Bursts (GRBs) have been conventionally bifurcated into two distinct categories: "short" and "long" with durations less than and greater than two seconds respectively. However, there is a lot of literature (although with conflicting results) regarding the existence of a third intermediate class. To investigate this issue, we extend a recent study by Kulkarni & Desai 2017a on classification of GRBs to two dimensions by incorporating the GRB hardness in addition to the observed durations. We carry out t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The three subclasses classification scheme has been discussed in different aspects (Virgili et al 2009;Bhave et al 2017;Svinkin et al 2019;Horváth et al 2019). Classifying LGRBs based on hardness ratio, peak flux, or luminosity have similar conclusions as our analysis.…”
Section: Summary and Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The three subclasses classification scheme has been discussed in different aspects (Virgili et al 2009;Bhave et al 2017;Svinkin et al 2019;Horváth et al 2019). Classifying LGRBs based on hardness ratio, peak flux, or luminosity have similar conclusions as our analysis.…”
Section: Summary and Discussionsupporting
confidence: 69%
“…2008;Guoshen Yu et al 2012). Gaussian distributions have been adopted by many GRB classification studies (Chattopadhyay & Maitra 2017;Svinkin et al 2019;Bhave et al 2017;Tarnopolski 2019a,b). In this work, we assume the distributions of each subclass of GRBs to be Gaussian in logarithmic space and use GMM to derive the properties of the overall population from those subclasses.…”
Section: Gaussian Mixture Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering of the duration and hardness of Swift/BAT GRBs [53,54] and the clustering of light curve shape indicators [55] identified three classes of bursts. Gaussian Mixture Modelbased (GMM) clustering applied to the Fermi/GBM sample revealed that GRB 170817A fit within the intermediate class in the duration-hardness plane [56], and that five classes could be identified by clustering spectral fit parameters, fluences, and durations [57].…”
Section: Introductionmentioning
confidence: 99%
“…Chattopadhyay & Maitra (2017) even found five kinds of GRBs in the BATSE catalog using Gaussian Mixture model. However, some recent works still insisted on two components (Tarnopolski 2015(Tarnopolski , 2016Zhang et al 2016a;Yang et al 2016b;Kulkarni & Desai 2017;Bhave et al 2017), and showed the intermediate GRB class is unlikely. The plausible explanation of the duration bimodal distribution is that the two-class GRB duration distributions are intrinsically non-symmetrical (Tarnopolski 2016).…”
Section: Introductionmentioning
confidence: 99%